TPA network for small food processors - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The TPA network for technologies and partnership in food processing was set up in 1988 by individuals involved in the development of food processing in the South. It is run by a network secretariat based at GRET, the French research and technology...